A narrative evaluation of a faith-based aftercare program for youth involved in the juvenile justice system. (March 2023) - Ferolino, Austin JP; Yap, Reuel Joab C
This study reports on the preliminary outcome evaluation of the Magone Home Aftercare Program (MHAP), a faith-based juvenile justice residential facility in the Philippines that provides intensive aftercare treatment for adolescent males involved in the juvenile justice system after their time in a rehabilitation facility or community detention in their area of residence. Although evaluation studies are typically conducted using quantitative research methods, we believe a narrative research approach can be a useful methodology that elucidates " why " and " how " or " the story " behind the success of the program. As such, we evaluated the effectiveness of the MHAP in facilitating the reintegration of its beneficiaries through the stories they tell. Particularly, we analyzed and compared the life stories of MHAP beneficiaries who have been successfully reintegrated into their respective communities within the frame of redemptive narrative identity. The analysis of the interview data revealed that the life stories of these former beneficiaries contained redemption scenes in which they drew on adverse childhood experiences (extreme poverty, parental neglect, abuse, abandonment, and crime) in realizing their true selves (by gaining wisdom from the past, opportunities, new sources of strength, and desire to help others). Importantly, the redemption narratives also contained key life episodes that recognized the MHAP as the key to their successful reintegration into society. Such findings provide valuable information (i.e. how the program has achieved its objectives) to all levels of the MHAP, from program beneficiaries and front-line staff to decision-makers and funders, as well as community partners.